Analytical chemistry. - Christian, Gary D.; Dasgupta, Purnendu K.; Schug, Kevin (Hoboken, NJ : John Wiley and Sons, Inc., 2014)
"The 7th Edition of Gary Christian's Analytical Chemistry focuses on more in-depth coverage and information about Quantitative Analysis (aka Analytical Chemistry) and related fields. The content builds upon previous editions with more enhanced content that deals with principles and techniques of quantitative analysis with more examples of analytical techniques drawn from areas such as clinical chemistry, life sciences, air and water pollution, and industrial analyses"--
Includes index.
Keywords: Chemistry, Analytic -- Quantitative -- Textbooks; SCIENCE / Chemistry / Analytic